PHYLOGENETIC RELATIONSHIPS AND REVIEW OF THE SPECIES OF AURICULARIA (FUNGI: BASIDIOMYCETES) IN COLOMBIA - Montoya-Alvarez Andrés Felipe (Caldasia)
The phylogenetic relationship of the species of the genus Auricularia and its allied taxa were investigated using the internal transcribed spacer (ITS) sequences of nuclear DNA. A molecular phylogenetic tree constructed using a total of 17 samples representing five species and two outgroups indicate that the species of Auricularia form a monophyletic group. Within the genus Auricularia, A. mesenterica is basal and the remaining Auricularia species form three clades; first clade consisted of A. auricula-judae; the second clade of A. fuscosuccinea, and the third clade of A. polytricha.